2012
DOI: 10.1021/ol3012666
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Synthesis of α,β-Disubstituted α,γ-Diaminophosphonic Acid Precursors by Michael Addition of α-Substituted Nitrophosphonates to Nitroolefins

Abstract: Michael additions of α-substituted nitrophosphonates to various nitroolefins are shown to proceed with high diastereo- and enantioselectivity when catalyzed by a quinine-derived thiourea-tertiary amine bifunctional catalyst and generate α,γ-diaminophosphonic acid precursors with contiguous quaternary and tertiary stereocenters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Two complementary methods, reported by Jørgensen10 and Alexakis,11 for the organocatalyzed 1,4‐addition of soft carbon nucleophiles to highly activated vinyl bis‐phosphonates have been described, as well as an intramolecular Stetter reaction that employed N‐heterocyclic carbenes as catalysts 12. Recently, the organocatalyzed Michael addition of α‐substituted nitrophosphonates to nitroolefins13 and trimethylphosphonoacetate to α,β‐unsaturated aldehydes14 has been described. Chiral β‐substituted alkylphosphonates have been prepared by using Rh‐catalyzed asymmetric hydrogenation of the corresponding β‐disubstituted α‐β‐unsaturated phosphonates15 and through a Cu‐catalyzed asymmetric conjugate reduction 16…”
Section: Introductionmentioning
confidence: 99%
“…Two complementary methods, reported by Jørgensen10 and Alexakis,11 for the organocatalyzed 1,4‐addition of soft carbon nucleophiles to highly activated vinyl bis‐phosphonates have been described, as well as an intramolecular Stetter reaction that employed N‐heterocyclic carbenes as catalysts 12. Recently, the organocatalyzed Michael addition of α‐substituted nitrophosphonates to nitroolefins13 and trimethylphosphonoacetate to α,β‐unsaturated aldehydes14 has been described. Chiral β‐substituted alkylphosphonates have been prepared by using Rh‐catalyzed asymmetric hydrogenation of the corresponding β‐disubstituted α‐β‐unsaturated phosphonates15 and through a Cu‐catalyzed asymmetric conjugate reduction 16…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Mukherjee et al reported an enantio-and diastereoselective synthesis of a,g-dinitrophosphonates 257 by quinine-thiourea C12-mediated Michael addition of nitrophosphonates 252 to nitroolefins 37 (Scheme 85). [110] Michael adducts 257 were obtained in moderate to good yields and diastereoselectivities and with excellent enantioselectivities in most cases. Subsequent reduction of an a,g-dinitrophosphonate (257, R= Me, R 1 = Ph) using NiCl 2 and NaBH 4 provided pyrazolidinyl phosphonate 258 in good yield.…”
Section: Càc Bond Formationmentioning
confidence: 95%
“…Sulfonamides are among the most powerful and important catalysts that can be derived from cinchona alkaloids . The secondary alcohol of a cinchona alkaloid can be easily converted into an amine by Mitsunobu‐type azide formation, followed by a Staudinger reduction ,. The amino group may be further modified to incorporate a sulfonamide group.…”
Section: Introductionmentioning
confidence: 99%